2012
DOI: 10.1007/s00384-012-1550-3
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-124 is an independent prognostic factor in patients with colorectal cancer

Abstract: Purpose Recently, has been demonstrated as a potential tumor suppressor in several types of cancers. However, the role of miR-124 in colorectal cancer remains unclear. This study was aimed at investigating the clinicopathological significance of miR-124 expression in colorectal cancer. Conclusions MiR-124 may play a certain role in the development of colorectal cancer. The downregulation expression of miR-124 is an independent prognostic factor in patients with colorectal cancer. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Its mature sequence is processed from three precursor variants that are located at chromosomes 8p23.1 (miR-124-1), 8q12.3 (miR-124-2) and 20q13.33 (miR-124-3), respectively. Studies have shown that miR-124 is down-expressed in various types of cancer, which is inversely associated with tumor growth, lymph node metastasis, and poor prognosis [1822]. However, there are studies that show different expression patterns and functions of miR-124 in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Its mature sequence is processed from three precursor variants that are located at chromosomes 8p23.1 (miR-124-1), 8q12.3 (miR-124-2) and 20q13.33 (miR-124-3), respectively. Studies have shown that miR-124 is down-expressed in various types of cancer, which is inversely associated with tumor growth, lymph node metastasis, and poor prognosis [1822]. However, there are studies that show different expression patterns and functions of miR-124 in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, investigation of miRNAs would be useful to expand our insight to better understand colorectal carcinogenesis as a potential tumor oncogene by analyzing associated mRNA targets and miRNA-mediated pathways. 21,22 There are many reports on the effects of miRNAs on oncogenes and tumor suppressor genes. 23 One study showed that down regulation of miR-383 was correlated with enhanced proliferative activity of germ cells in maturation arrest patients.…”
Section: Capability Of Mir-383 To Function As a Colorectal Cancer Tummentioning
confidence: 99%
“…5 Therefore, knowing more about the biology and nature of colorectal cancer, it is possible to design effective prognostic, diagnostic, and treatment plans to help reduce the rate of this disease. 6 MicroRNAs (miRNAs) are a class of small (18)(19)(20)(21)(22)(23)(24) noncoding RNAs that regulate gene expression at post translation levels. 7,8 This molecular RNAs regulate many biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, downregulated miR-124 expression was previously identified in patients with breast cancer, 25 clear-cell renal cell carcinoma, 26 cervical cancer, 27 and colorectal cancer, 28 and these studies show that decreased miR-124 expression closely correlated with poor clinical outcomes. Consistent with these reports, our clinical data also show that the expression of miR-124 level negatively correlated with the overall survival of NSCLC patients, and our multivariate analysis indicates that miR-124 may be a useful independent biomarker for predicting NSCLC disease progression.…”
Section: Discussionmentioning
confidence: 63%